Implementation of Regent Regulation Number 19 of 2023 Against Early Marriage Rates in Bojonegoro Regency (Case Study of Bojonegoro Religious Affairs Office) - Afif Fadhlurrahman; Waluyo (YUSTISIA MERDEKA : Jurnal Ilmiah Hukum, 2024)
Abstract Introduction to the Problem: The impact of early marriage on children is also seen in the risk of a large psychological condition because mentally almost all of them are not ready to assume great responsibility in fostering family relationships so that it can lead to divorce, even from a health perspective a woman who marries under the age of 20 is at risk of cervical cancer because she is a teenager. Bojonegoro Regency is one of the districts in the spotlight related to the high rate of early marriage in East Java, Bojonegoro Regency is included in the top 10 high marriage rates in East Java. Purpose/Study Objectives: This study aims to find out about how the implementation of marriage incentives at the Bojonegoro Regency Religious Affairs Office based on the Regent's Regulation and to find out how the impact analysis of Regent's Regulation Number 19 of 2023 on the level of early marriage in Bojonegoro Regency. Design/Methodology/Approach: The method used in this research is empirical juridical which is focused on examining phenomena that occur in the field and making it the main source of data, such as the results of interviews and also the results of field studies. Which uses a qualitative approach and field study data analysis. Findings: The results showed that the implementation of the provision of Marriage Capability Incentives is in accordance with Law Number 16 of 2019 concerning Marriage, and Regent Regulation Number 19 of 2023 concerning the provision of marriage capability incentives, but even so it is not enough to reduce the high rate of early marriage in Bojonegoro Regency. Paper Type: Research Article